Tindak Pidana Penipuan Oleh Promotor Penyelenggara Konser (Studi Kasus Konser We All Are One) - Nabila, Najwa Vira (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Korean culture has spread throughout the world, including Indonesia, which is one of the countries with the highest K-Pop fans. The rise of K-Pop fans in Indonesia presents music concerts as a place to bring fans together with their idols. K-Pop concerts held in a country are generally arranged by the promoter. However, sometimes promoters are negligent or deliberately commit criminal acts of fraud that harm fans who have bought concert tickets to watch their idols. The promoter's responsibility to fans must be carried out according to existing regulations. This research is aimed at finding out and analyzing criminal acts of fraud committed by the promoter of the K-Pop concert We All Are One who is a foreign citizen, as well as the responsibilities of a promoter towards his consumers.